Identification of critical buses in the Sulbagsel electrical system network integrated with wind power plants - Ilyas, Andi Muhammad; Siswanto, Agus; Rahman, Muhammad Natsir (International Journal of Electrical and Computer Engineering (IJECE), 2026)
The growing deployment of renewable energy has become increasingly important as conventional fossil-based generation faces sustainability and resource limitations. On Sulawesi Island, Indonesia, wind energy contributes to the regional grid through several wind power plants, whose fluctuating generation introduces operational concerns for system stability. This study investigates the stability performance of the Sulbagsel 78-bus network by pinpointing vulnerable buses and examining the effects of wind power variability. A hybrid stability index (HSI), which integrates multiple stability indicators, is applied to obtain a more robust assessment. The analysis shows that the entire system operates within a secure margin, with all index values remaining below the critical limit (<1). The most sensitive areas are located on the transmission paths connecting Bus 56 Sidera–Bus 57 Sidera 70 kV (0.02268), Bus 38 Bosowa–Bus 40 Pangkep (0.02220), and Bus 73 Powatu 150 kV–Bus 74 Powatu 70 kV (0.02187). In contrast, the Bus 24 Tanjung Bunga–Bus 25 Bontoala corridor demonstrates the strongest stability margin (0.00026). These results indicate that the variability of wind generation does not impose significant negative impacts on the overall stability of the Sulbagsel power system.